(untitled) (Historia, 2021)
Since the early 1990s there has been a steady rise in the publication of biographies, auto-biographies and memoirs of struggle stalwarts who played a significant role in the liberation struggle in South Africa. These publications have undoubtedly enriched our understanding of the liberation struggle in South Africa and the enormous sacrifices many individuals made to achieve freedom.